Redistribution of total reactive nitrogen in the lowermost Arctic stratosphere during the cold winter 2015/2016 - Ziereis, Helmut; Hoor, Peter; Grooß, Jens-Uwe; Zahn, Andreas; Stratmann, Greta; Stock, Paul; Lichtenstern, Michael; Krause, Jens; Bense, Vera; Afchine, Armin; Rolf, Christian; Woiwode, Wolfgang; et al. (Atmospheric Chemistry and Physics, 2022)
Aircraft borne observations were conducted in the lowermost Arctic stratosphere during the winter of 2015/2016. The observed distribution of reactive nitrogen shows clear indications of nitrification in mid-winter and de-nitrification in late winter. This was caused by the formation of polar stratospheric cloud particles, which were observed during several flights. The sedimentation and evaporation of these particles and the descent of air masses cause a redistribution of reactive nitrogen.